Three-dimensional friction measurement during hip simulation - Sonntag, Robert (PLoS One, 2017)
OBJECTIVES: Wear of total hip replacements has been the focus of many studies. However, frictional effects, such as high loading on intramodular connections or the interface to the bone, as well as friction associated squeaking have recently increased interest about the amount of friction that is generated during daily activities. The aim of this study was thus to establish and validate a three-dimensional friction setup under standardized conditions. MATERIALS AND METHODS: A standard hip simulator was modified to allow for high precision measurements of small frictional effects in the hip during three-dimensional hip articulation. The setup was verified by an ideal hydrostatic bearing and validated with a static-load physical pendulum and an extension-flexion rotation with a dynamic load profile. Additionally, a pendulum model was proposed for screening measurement of frictional effects based on the damping behavior of the angular oscillation without the need for any force/moment transducer. Finally, three-dimensional friction measurements have been realized for ceramic-on-polyethylene bearings of three different sizes (28, 36 and 40 mm). RESULTS: A precision of less than 0.2 Nm during three-dimensional friction measurements was reported, while increased frictional torque (resultant as well as taper torque) was measured for larger head diameters. These effects have been confirmed by simple pendulum tests and the theoretical model. A comparison with current literature about friction measurements is presented. CONCLUSIONS: This investigation of friction is able to provide more information about a field that has been dominated by the reduction of wear. It should be considered in future pre-clinical testing protocols given by international organizations of standardization.